Fracture behavior of SiCf/SiC cladding with prefabricated cracks on the inner/outer wall - Ze-Xi Zhang; Chuang-Tian Zhan; Yang-Qing Liu; Zhen-Quan Liang; Wei-Ming Guo; Shi-Kuan Sun; Yun Li; Li-Xiang Wu; Jia-Xiang Xue; Hua-Tay Lin (Journal of Materials Research and Technology)
This study investigated the fracture behavior of SiCf/SiC cladding with axial cracks in the CMC layer/monolithic SiC layer on the inner and outer wall via an expanding plug test. The specimen with a prefabricated crack on the outer wall fractured in no specific direction. After the first load drop, fracture sources can be detected not only near the notch but also in other directions within the CMC layer. The simulation shows a homogeneous stress distribution resulting in a similar hoop strength to the specimen without prefabricated cracks. In contrast, the specimen with a prefabricated crack on the inner wall fractured along the notch. After the first load drop, fracture sources can be detected only near the notch. The simulation demonstrates stress concentration, resulting in a lower hoop strength. Therefore, considering the nuclear application of SiCf/SiC cladding, we are supposed to pay more attention to the defects in CMC layer in the fabrication process of SiCf/SiC cladding.